Elastic stable intramedullary nailing for displaced proximal humeral fractures in older children - Rajan, Rohan Ananda (Springer Berlin Heidelberg, 2007)
PURPOSE: To demonstrate the effectiveness of intramedullary fixation of severely displaced proximal humeral physeal fractures in skeletally immature children using the elastic stable intramedullary nail (ESIN). METHODS: Retrospective recruitment of 14 patients aged 10–15-years old with severely displaced proximal humeral physeal fractures between 1999 and 2004 in a single regional specialist paediatric orthopaedic hospital. The fractures were graded using the Neer classification; severe displacement constituted Neer II–IV or displacement >1 cm and angulation >45°. Patients were followed up and assessed using the Disabilities of the Arm, Shoulder and Hand score (DASH) and the Neer Shoulder score. Radiographs were assessed for deformity. Subjective satisfaction was assessed. RESULTS: Fourteen patients with mean follow-up of 30 months (12–66 m) from surgery. All fractures were radiologically united at a median time of eight weeks (7–10 weeks). At follow-up, Neer Shoulder mean score was 96.79 (range 83–100) and DASH mean score 2.26 (0–7.5). Subjectively 71% were very satisfied and 29% were satisfied. CONCLUSIONS: We commend stabilisation using ESIN in the management of the displaced proximal humeral physeal fracture in older children, once reduction of the fracture has been achieved by either closed or open means. ESIN is safe and allows early return to pre-injury function.